Differential expression of the HvCslF6 gene late in grain development may explain quantitative differences in (1,3;1,4)-β-glucan concentration in barley - Wong, Sie Chuong; Shirley, Neil J.; Little, Alan; Khoo, Kelvin H. P.; Schwerdt, Julian; Fincher, Geoffrey B.; Burton, Rachel A.; Mather, Diane E. (Springer, 2015)
The cellulose synthase-like gene HvCslF6, which is essential for (1,3;1,4)-β-glucan biosynthesis in barley, collocates with quantitative trait loci (QTL) for grain (1,3;1,4)-β-glucan concentration in several populations, including CDC Bold × TR251. Here, an alanine-to-threonine substitution (caused by the only non-synonymous difference between the CDC Bold and TR251 HvCslF6 alleles) was mapped to a position within HvCSLF6 that seems unlikely to affect enzyme stability or function. Consistent with this, transient expression of full-length HvCslF6 cDNAs from CDC Bold and TR251 in Nicotiana benthamiana led to accumulation of similar amounts of (1,3;1,4)-β-glucan accumulation. Monitoring of HvCslF6 transcripts throughout grain development revealed a significant difference late in grain development (more than 30 days after pollination), with TR251 [the parent with higher grain (1,3;1,4)-β-glucan] exhibiting higher transcript levels than CDC Bold. A similar difference was observed between Beka and Logan, the parents of another population in which a QTL had been mapped in the HvCslF6 region. Sequencing of a putative promoter region of HvCslF6 revealed numerous polymorphisms between CDC Bold and TR251, but none between Beka and Logan. While the results of this work indicate that naturally occurring quantitative differences in (1,3;1,4)-β-glucan accumulation may be due to cis-regulated differences in HvCslF6 expression, these could not be attributed to any specific DNA sequence polymorphism. Nevertheless, information on HvCslF6 sequence polymorphism was used to develop molecular markers that could be used in barley breeding to select for the desired [low or high (1,3;1,4)-β-glucan] allele of the QTL.